LEGAL CERTAINTY OF INHERITANCE BPHTB COLLECTION BY BAPENDA MALANG CITY - Sandi Permana Nugraha; Tunggul Anshari Setia Negara; Dyah Widhiawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
In the provisions of Article 7 paragraph (2) letter e of the Malang City Regional RegulationNumber 15 of 2010 concerning BPHTB Malang City, there are no further regulations regarding the definition of market value, who is authorized to determine market value and how the mechanism for determining it. Thus causing the market value in Article 7 paragraph (2) letter e to be interpreted freely (multiple interpretations). The purpose of this study is to analyze and find out how legal certainty determines market value in the collection of BPHTB Inheritance by Bappenda in Malang City. The results of the study show that market value regulation in the Perda BPHTB Malang City does not guarantee legal certainty. This has an impact on the violation of the principles of BPHTB collection which includes the principles of justice, legal certainty, legality, and simplicity. In addition, legal uncertainty regarding market value regulation has led to acts that exceeded the authority in collecting BPHTB conducted by Bapenda Malang City.